Direction in Student-Centered Arabic Language Learning: The Actualization of Discovery Learning - Bambang Prasetyo; Kemas Muhammad; Nazarmanto Nazarmanto; Febri Yansyah; Resti Adelicka Anggraini; Nadila Hanisaniyya; Siti Robiatul Adawiyah (Universitas Ahmad Dahlan, 2026)
Arabic language learning occupies a strategic position in education but still faces complex challenges, particularly the dominance of teacher-centered learning methods. Discovery learning emerges as a solution by encouraging students to become more active through independent inquiry, integrating the four language skills, and promoting a student-centered learning approach. This study employs a mixed-method design with an explanatory sequential approach, combining qualitative and quantitative analyses. Data were collected through observation, interviews, questionnaires, documentation, and tests. Qualitative data were analyzed through data reduction, presentation, and conclusion drawing, while quantitative data were analyzed using normality testing, N-Gain, and hypothesis testing. The findings reveal that before implementing discovery learning, students experienced difficulties understanding Arabic, teachers did not prepare written lesson plans, and evaluation focused mainly on grammar, translation, and vocabulary. After implementation, learning shifted to a student-centered model where students became more active and engaged. The application of discovery learning also enhanced conceptual understanding, learner autonomy, and academic achievement. This improvement was demonstrated by a significant difference between the pre-test mean score of 36.5 and the post-test mean score of 82.8, with hypothesis testing results of 0.000 < 0.05. Therefore, the implementation of discovery learning has a positive and significant impact on Arabic language learning outcomes.